Digital ethnography on augmented reality and learning physics - Tayco, Ryan Jhun Orillano
The study aimed to determine the appropriateness of Augmented Reality's presence on learning materials on students learning motivation of Grade 8 Junior high school in science in an online learning environment. Moreover, it determined the augmented reality components that affect the increase in students learning motivation, the challenges that may compromise the acceptability of the students to augmented reality, and determine the design of the augmented reality digital content to improve student's learning motivation and learning outcomes in an online learning environment. The study was conducted in a public high school in Quezon City during the fourth quarter of the online distance learning modality for the school year 2020-2021. The participants from grade 8 science classes were selected, and the Augmented Reality learning material-digital content was developed and enhanced using EyeJack App creator. The ARCS model of the motivational design that will primarily assess students' motivation was adopted. The researcher used a semi-structured interview with open-ended questions to collect data and enriched using data collection by qualitative research instrument of empathy map of each participant and researchers field notes during online observation in the duration of the short-term digital ethnography. The findings revealed that students' learning motivation was influenced by augmented reality digital content present on learning material; participants indicated that aspects of attention, relevance, confidence, and satisfaction towards their learning motivation during intervention was increased by the element of augmented reality in learning material, these were determined through Keller's ARCS model of motivational design. Challenges that compromise the acceptability of augmented reality in students' learning motivation were determined: accessibility issues, occasional usage, limited exploration time, and technical issues. These factors seemed most determinative in compromising AR's effectiveness as a tool to increase student motivation. Despite those identified factors, this research study finds the augmented reality features that could help improve students' learning motivation and outcome overall; aspect of functionality felt, the thrill experienced during exploration, and phenomena enhancing their user experience. The researcher also identified that attributes like excitement, collaboration, ease of usage, inclusivity, and accessibility are significant elements needed in developing a comparable learning material in the future.